The Relationship of Health Workers' Workload with The Quality of Interpersonal Communication Services at the West City Health Center - Marlin Giu; Herlina Jusuf; Suardi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The workload of health workers at the West City Health Center is characterized by high patient visits, limited number of officers, and administrative tasks that must be completed simultaneously. This condition often causes work pressure and has the potential to disrupt interpersonal communication in the ministry. This study aims to determine the relationship between the workload of health workers and the quality of interpersonal communication in services at the West City Health Center. The type of quantitative research with the analytical survey method uses a cross-sectional design. The research population of all health workers at the West City Health Center amounted to 58 health workers with a total sampling technique. Data collection using workload questionnaires and interpersonal communication quality questionnaires. Data analysis using the Spearman's Rank test. Based on data analysis, it was shown that there was no relationship between workload variables and the quality of interpersonal communication in health workers at the West City Health Center with the Spearman's Rank test value p-value = 0.428 (P > 0.05), there was no relationship between workload and the quality of interpersonal communication. In conclusion, even though the workload is quite high, health workers at the West City Health Center continue to carry out interpersonal communication well between health workers in the service. Suggestions, health workers are expected to maintain effective, empathetic, and open communication with patients and colleagues.